ANALYSIS AND INITIATION OF EFFORTS TO EXTERMINATE ILLEGAL INDONESIAN MIGRANT WORKERS SYNDICATE THROUGH COLLABORATION OF THE INDONESIAN MIGRANT WORKERS PROTECTION AGENCY AND THE DIRECTORATE GENERAL OF IMMIGRATION - Atsil Syah Gibran; M Fadly Khusairy (Journal of Law and Border Protection, 2023)
The Indonesian Migrant Worker Protection Agency (BP2MI) has made efforts to combat illegal placement of PMIs through outreach and regulatory adjustments. The number of PMI placements continued to increase, with 25,973 placements in May 2023 compared to 11,022 in May 2022 and 6,264 in May 2021. The majority of PMI placements in May 2023 were in the formal sector (55%) compared to the informal sector (45%). Efforts to impose sanctions BP2MI head of BP2MI has proposed firm action against illegal PMI placement syndicates, including cooperation with the immigration agency and the use of a special identity in PMI passports. Further research is needed to analyze and initiate efforts to eradicate illegal PMI syndicates through a review of the role of immigration, in order to address the challenges faced by PMI and the role of immigration authorities in combating illegal placements.